2016
DOI: 10.1002/nag.2555
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of projectile penetration and perforation of plain and fiber reinforced concrete slabs

Abstract: Summary The research presented in this paper deals with the numerical analysis of projectile impact on regular strength concrete (RSC), high‐strength concrete (HSC), and engineered cementitious composites (ECC) using the Lattice Discrete Particle Model (LDPM). The LDPM is chosen in this study as it naturally captures the failure mechanisms at the length scale of coarse aggregate of concrete, and its capabilities include the accurate depiction of both intrinsic and apparent rate effects in concrete, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…This concept is based on the bond distribution of the microstructure of the material, which is assumed to follow a Maxwell-Boltzmann distribution, and their breakage and restoration rates. More specifically, the equation derived by Bažant scales vertically the cohesive behavior of the material and has been successfully used by Di Luzio [12] and Boumakis et al [11] for modeling failure under low strain rates as observed for tertiary creep, and by Smith and Cusatis [52] for failure at the high strain rates characteristic of e.g. projectile impact in concrete.…”
Section: Rate-theory Based Relationmentioning
confidence: 99%
“…This concept is based on the bond distribution of the microstructure of the material, which is assumed to follow a Maxwell-Boltzmann distribution, and their breakage and restoration rates. More specifically, the equation derived by Bažant scales vertically the cohesive behavior of the material and has been successfully used by Di Luzio [12] and Boumakis et al [11] for modeling failure under low strain rates as observed for tertiary creep, and by Smith and Cusatis [52] for failure at the high strain rates characteristic of e.g. projectile impact in concrete.…”
Section: Rate-theory Based Relationmentioning
confidence: 99%
“…This variation can be explained by three main mechanisms: (1) the creep of the material, (2) rate effect on the bond rupture, and (3) the effect of inertia in the crack propagation. For quasi-static tests, typically the loading rate˙ lies in between 10 −7 and 10 −3 s −1 [59], and whithin this strain rate range, the first two mechanisms mentioned above are dominant. Therefore, except the creep rate, also the rate dependency of the crack opening has to be taken into account.…”
Section: Rate Effectmentioning
confidence: 99%
“…The above concept has been implemented in LDPM [59] by scaling the stressstrain boundary, defined in Eq. 7 by the function F (˙ ) as…”
Section: Rate Effectmentioning
confidence: 99%
“…Protective works provide a credible defense against conventional weapons [1]. As shown in Figure 1, protective works typically consists of a camouflage layer, a shelter layer, a distribution layer and a support structure [2].…”
Section: Introductionmentioning
confidence: 99%